Comparison of Second-Trimester Uterine Artery Doppler Indices between Pregnant Women with and without Prior Cesarean Delivery and Effect on Perinatal Outcomes: Uterine Artery Doppler Indices in Pregnancy - Chaiprasit, Bundaree; Mataneedol, Suthasinee; Smanchat , Buppa; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun (Siriraj Medical Journal, 2024)
Objective: To evaluate the effects of prior cesarean delivery on second-trimester Uterine Artery (UtA) Doppler and its effect on perinatal outcomes. Materials and Methods: This study was conducted at the Maternal Fetal Medicine unit of Bhumibol Adulyadej Hospital, Thailand between June 2023 and January 2024. Healthy pregnant women aged between 18 and 45 years old were recruited and divided into prior (PCD) and non-prior cesarean delivery (non-PCD) groups. Both groups underwent UtA Doppler study from 18 to 24 weeks of gestation. UtA Doppler indices consisted of pulsatility index (UtA-PI), resistance index (UtA-RI) and systolic/diastolic ratio (S/D). Demographics, maternal and neonatal outcomes were collected. Results: Total of 416 participants were recruited and divided equally. The mean age of participants was 30.5 years old. Diabetes mellitus in pregnancy and hypertensive disorder were reported as 18.9 (79/416) and 5.5 (23/416) percent, respectively. From univariate analysis, subjects in the PCD group had higher UtA-PI, UtA-RI and UtA S/D than the non-PCD group with statistical significance. After multiple logistic regressions, only UtA-RI was greater in the PCD group with any statistical significance. The mean gestational age at delivery was 38.41 weeks. Prevalence of small for gestational age deliveries, preeclampsia, and preterm birth were 4.4 (17/376), 3.1 (12/376) and 10 percent (38/376), respectively. Maternal and neonatal outcomes of both groups were comparable. Number of cesarean deliveries, parity, miscarriage, and anterior placentation were not associated with UtA Doppler indices. Conclusion: UtA-RI of prior cesarean delivery participants were higher than non-prior cesarean delivery participants and not associated with maternal and neonatal adverse outcomes.